Displaced Persons from the Baltic States in Northern Germany: The case of Lübeck and Flensburg - Pletzing, Christian (Genocidas ir rezistencija, 2025)
The history of displaced persons (DPs) in Germany has been studied extensively since the 1980s, with the focus on Jewish, Polish and Soviet DPs. However, the unique experiences in Germany of the Baltic DPs – Estonians, Latvians and Lithuanians – have received little attention. This paper examines the history of Baltic DPs in Northern Germany, particularly in the cities of Lübeck and Flensburg, using local archival sources and Latvian DP camp newspapers.Due to its location on the border between the British and Soviet occupation zones, Lübeck became a central hub for refugees. By the end of 1945, the city was home to approximately 11,580 Baltic DPs – a significant portion of the 53,800 Baltic DPs in the British occupation zone. Many Baltic DPs were initially put up in private housing, but were later moved to DP camps. In Flensburg, a smaller but notable Baltic DP population existed, with 1,254 Latvians, 928 Estonians and 784 Lithuanians registered in 1945.The living conditions in the DP camps varied greatly. Some camps provided adequate shelter, while others were overcrowded and lacked basic sanitation. Over time, authorities attempted to segregate the camps by nationality. Many Baltic DPs engaged in cultural and educational activities, forming their own schools, newspapers and institutions.Baltic DPs were generally viewed more favourably than other DP groups, such as the Polish or Soviet DPs, due to cultural similarities. However, tensions arose over housing shortages and the forced confiscation of German property for DP accommodations.The Baltic DPs enjoyed a vibrant cultural scene in Lübeck, including theatre performances, choirs and sporting events. DP newspapers played a crucial role in maintaining national identity and communication.With the handover of the DP camps to the German administration in 1950, the remaining displaced persons were reclassified as ‘homeless foreigners’. Children were required to attend German schools, and vocational training programmes were set up to facilitate  employment.The last DP camp in Schleswig-Holstein closed in 1966, marking the end of an era.
Keywords: Displaced persons; Northern Germany; housing; culture; organisations; newspapers; Baltic-German relations